Impact of ultrasound-guided percutaneous flexor retinaculum fenestration on outcome of hydrostatic dissection of median nerve in patient with carpal tunnel syndrome - Ahmed M. Zidan; Hytham Mohamed Nafady; Mohamed Abdelrahman Alkenawy; Mohammad Abol Wafa Ahmad; Ahmed Mohamed Eldeeb; Mohamed Talaat Mohamed; Mahmoud Mohamed Aboumandour Fouda; Hasan A. Soltan; Nehal Elsayed Shabaan; Ahmed B. M. Mehany; Yasser Fouad Ghoraba (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Most cases of entrapment neuropathy are due to median nerve compression, which manifests most commonly as carpal tunnel syndrome (CTS). There are several nonsurgical treatment options available for mild-to-moderate circumstances. Aim To assess the effect of ultrasound-guided percutaneous flexor retinaculum fenestration on the outcome of hydrostatic dissection of the median nerve in cases with CTS. Methods This randomized clinical research included a total of 54 individuals with CTS separated into two groups; group (A) included patients with hydrostatic dissection with adjuvant fenestration of transverse carpal ligament (n = 27), while group (B) involved patients with hydrostatic dissection alone (n = 27). Pain and disability through the visual analog scale (VAS), symptom severity (SS) score, modified Boston Carpal Tunnel Questionnaire (BCTQ), and functional disability (FD) score before injection and 3 months post-injection were assessed. Distal motor latency (DML) and sensory conduction velocity (SCV) were measured at baseline and 3 months after the procedure. Results SS and FD scores, were comparable in both groups before the procedure, while after three months of the procedure, the mean of SS and FD scores was significantly higher in group A (24.18 ± 3.62 and 17.52 ± 2.15, respectively) than in group B (16.55 ± 3.17and 11.39 ± 1.81, respectively) (p < 0.001). Also, there was a significant distinction between before and after the procedure in both groups (p < 0.001). Regarding electro physiologic outcomes, DML and SCV were comparable in both groups before the procedure, while after three months of the procedure, the mean of DML and SCV scores was significantly higher in group A (4.41 ± 0.41 and 39.27 ± 2.35, correspondingly) than group B (4.23 ± 0.37and 42.55 ± 2.75, respectively) (p = 0.011 and < 0.001, correspondingly). Also, there was significant variance between before & after the procedure in both groups (p = 0.010 and < 0.001, correspondingly). Conclusion Ultrasound-guided hydro-dissection and fenestration of the transvers carpal ligament is a simple, non-invasive treatment for CTS that has the potential to reduce symptoms for a long time and delay or perhaps prevent the need for open release.